The concept, content and system of principles of civil protection at the regional level - Ostapiuk, A. Yu.; Остап'юк, А. Ю. (Legal, Economic Science and Praxis. - 2023. - № 8. - P. 42-45, 2023)
Підкреслено, що принципи забезпечення цивільного захисту на регіональному рівні – це сукупність основних принципів, основних ідей, які визначають порядок правового регулювання, а також організації та практичної реалізації заходів цивільного захисту на території певної області. Зазначено, що законність, як фундаментальна ідея цивільного захисту на регіональному рівні, виражається в: по-перше, суворій безумовній відповідності процесу цивільного захисту в межах конкретного регіону на основі положень законодавчих, підзаконних та місцевих нормативних актів; по-друге, діяльність суб’єктів цивільного захисту виключно в межах прав та обов’язків, покладених на них нормами чинного законодавства; по-третє, відповідальність цих суб'єктів за порушення та прорахунки при здійсненні відповідних заходів Стверджено, що принципи забезпечення цивільного захисту на територіальному рівні, крім законності, повинні включати також наступні: принцип системності та наступності; принцип рівності та однаковості забезпечення цивільного захисту в межах територія області; принцип партнерства суб'єктів забезпечення публічної безпеки і порядку; принцип еволюції; принцип науковості.

It was concluded that the principles of providing civil protection at the regional level are a set of basic principles, basic ideas that determine the order of legal regulation, as well as the organization and practical implementation of civil protection measures on the territory of a certain region. It was noted that legality, as the fundamental idea of civil protection at the regional level, is expressed in: first, strict and unconditional compliance of the civil protection process within a specific region, based on the provisions of legislative, by-law and local regulatory acts; secondly, the activities of civil protection entities exclusively within the framework of the rights and obligations assigned to them by the norms of current legislation; thirdly, the responsibility of these subjects for violations and miscalculations in the implementation of relevant measures It is argued that, in addition to legality, the principles of providing civil protection at the territorial level should also include the following: the principle of systematicity and continuity; the principle of equality and uniformity of providing civil protection within the territory of the region; the principle of partnership of subjects ensuring public safety and order; principle of evolution; the principle of scientificity.

Подчеркнуто, что принципы обеспечения гражданской защиты на региональном уровне представляют собой совокупность основных принципов, базовых идей, определяющих порядок правового регулирования, а также организации и практической реализации мер гражданской защиты на территории определенного региона. Отмечено, что законность, как основополагающая идея гражданской защиты на региональном уровне, выражается: во-первых, в строгом и безусловном соблюдении процесса гражданской защиты в пределах конкретного региона, основанного на положениях законодательных, подзаконных и локальных нормативных актов; во-вторых, в деятельности субъектов гражданской защиты исключительно в рамках закрепленных за ними нормами действующего законодательства прав и обязанностей; в-третьих, в ответственности указанных субъектов за нарушения и просчеты при осуществлении соответствующих мер. Утверждено, что, помимо законности, к принципам обеспечения гражданской защиты на территориальном уровне следует отнести также следующие: принцип системности и непрерывности; принцип равноправия и единообразия обеспечения гражданской защиты на территории региона; принцип партнерства субъектов, обеспечивающих общественную безопасность и порядок; принцип эволюционности; принцип научности.
Keywords: принципи; принципи права; безпека; цивільний захист; регіональний рівень; principles; principles of law; security; civil protection; regional level; принципы; принципы права; безопасность; гражданская защита; региональный уровень